2002
DOI: 10.1039/b207713b
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating water exchange for GdIIIchelates by steric compression around the water binding site

Abstract: The water exchange process was accelerated for nine-coordinate, monohydrated macrocyclic GdIII complexes by inducing steric compression around the water binding site; the increased steric crowding was achieved by replacing an ethylene bridge of DOTA4- by a propylene bridge; in addition to the optimal water exchange rate, the stability of [Gd(TRITA)(H2O)]- is sufficiently high to ensure safe medical use which makes it a potential synthon for the development of high relaxivity, macromolecular MRI contrast agents. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
99
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 6 publications
2
99
0
Order By: Relevance
“…The steric strain was usually reached by introduction of one extra methylene group into the backbone (propylene group instead of ethylene bridge) or in one of the pendant arms (i.e. with propionate pendant instead of acetate), [8][9][10][11] or by substitution of ligand backbone by alkyl/aryl group. [12,13] The complexes formed with these new ligands are thermodynamically usually slightly less stable than those of H 4 dota and H 5 dtpa.…”
Section: Introductionmentioning
confidence: 99%
“…The steric strain was usually reached by introduction of one extra methylene group into the backbone (propylene group instead of ethylene bridge) or in one of the pendant arms (i.e. with propionate pendant instead of acetate), [8][9][10][11] or by substitution of ligand backbone by alkyl/aryl group. [12,13] The complexes formed with these new ligands are thermodynamically usually slightly less stable than those of H 4 dota and H 5 dtpa.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In order to enhance r 1 , it has been found that: 1) tumbling has to be slowed down by attaching the chelate to macromolecular assemblies, such as proteins, [2,3] dendrimers, [4,5] micellar aggregates [6,7] or polymers; [8] 2) the water-exchange rate has to be increased by promotion of the departure of a coordinated water molecule; this is achieved by the design of optimized chelates such as Gd III complexes of TRITA (1,4,7,10-tetraazacyclotridecane-1,4,7,10-tetraacetic acid), [9] EPTPA (ethylenepropylenetriaminepentaacetic Abstract: We report the study of binuclear Ln III chelates of OHEC (OHEC = octaazacyclohexacosane-1, 4,7,10,14,17,20,23-octaacetate). The interconversion between two isomeric forms, which occurs in aqueous solution, has been studied by NMR, UV/ Vis, EPR, and luminescence spectroscopy, as well as by classical molecular dynamics (MD) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The SolomonBloembergen-Morgan theory predicts maximum proton relaxivity when the water exchange is in a narrow, optimal range, and the rotation and electron spin relaxation are both slow. [4] Recently, the water-exchange rate has been successfully tuned to optimal values in poly(amino carboxylate) [5][6][7][8] and other stable complexes of Gd III . [9] In spite of the continuous work on the understanding of structure-mechanism relationships with regard to electron spin relaxation, it is not yet a straightforward matter to improve this factor through rational molecular design.…”
mentioning
confidence: 99%